2004
DOI: 10.1016/j.clpt.2003.11.108
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bioavailability of rifampicin and other anti-tb drugs in patients with advanced HIV disease

Abstract: Background Malabsorption of drugs from the gastro‐intestinal tract due to HIV enteropathy and concurrent infections could lower the bioavailability of anti‐tuberculosis (TB) drugs in HIV infected individuals. Our aim was to study the pharmacokinetics of rifampicin (RMP), isoniazid (INH), pyrazinamide (PZA) and ethambutol (EMB) in HIV infected Indian subjects. The D‐xylose absorption test was also performed in all the patients. Method We studied 13 patients with smear positive pulmonary TB, 13 with HIV & diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Earlier, we had shown that malabsorption of antituberculosis drugs occurs in patients with advanced HIV disease with and without diarrhea. 19 Adequate plasma concentrations of nevirapine that are not influenced by the stage of immune suppression, sex, and BMI observed in this study are encouraging. Hence, if patients take regular treatment, chances of failure due to inadequate drug levels are low.…”
supporting
confidence: 55%
“…Earlier, we had shown that malabsorption of antituberculosis drugs occurs in patients with advanced HIV disease with and without diarrhea. 19 Adequate plasma concentrations of nevirapine that are not influenced by the stage of immune suppression, sex, and BMI observed in this study are encouraging. Hence, if patients take regular treatment, chances of failure due to inadequate drug levels are low.…”
supporting
confidence: 55%
“…HIV infection has been reported to adversely impact anti-tuberculosis drug levels. 24 In view of the signifi cant correlations observed between C max , C 48h and AUC 0-24 of RBT and CD4 cell counts, one might consider increasing the RBT dose. A significant positive correlation between RBT and RTV C max , though unclear, further highlights the need to consider increasing RBT doses.…”
Section: Discussionmentioning
confidence: 99%
“…While HIV could influence outcome in different ways, inability to achieve and sustain therapeutic levels of anti-TB drugs (possibly due to malabsorption) could be a major factor in causing poor treatment outcomes and emergence of drug resistance. We have found evidence of malabsorption and decreased bioavailability of anti-TB drugs in patients with advanced HIV disease and TB [51].…”
Section: Factors Influencing Anti-tb Drug Pharmacokineticsmentioning
confidence: 97%
“…It has, therefore been suggested that the dosage of INH should be tailored based on age and possibly NAT2 genotype [16]. Studies done in adult HIV-TB coinfected patients showed that the blood levels of INH were more affected in rapid than slow acetylators of INH [51]. The impact of drug transporter polymorphisms on RMP exposure has also been reported [17,18].…”
Section: Factors Influencing Anti-tb Drug Pharmacokineticsmentioning
confidence: 98%